Photobiomodulation in restorative dentistry - Benetti, Francine; de Oliveira Gallinari, Marjorie [UNESP]; dos Santos Chaves, Hebertt Gonzaga; Soares Mendes, Ana Carolina; de Arantes, Lara Cancella; Moreira Carvalho, Gabriela Luiza; Maia, Caroline Andrade; Figueiredo, Barbara; dos Reis Prado, Alexandre Henrique; de Jesus, Witalo Pereira; Emerenciano Bueno, Carlos Roberto; Sandoval Cury, Marina Tolomei; et al. (My University, 2023)
Photobiomodulation therapy has gained increasing recognition in the fields of medicine and dentistry due to its notable analgesic effects, its capacity to modulate inflammation, and its ability to stimulate biological processes. For instance, the inflammation caused by dental bleaching, resulting from the penetration of reactive oxigen species into the dental pulp, can be minimized with the use of photobiomodulation. Additionally, acute dentin hypersensitivity, a painful and short-lasting pulp response to harmless extrinsic environmental stimuli, which can affect the quality of life related to a patient's oral health, can also be minimized with photobiomodulation. On the other hand, Photodynamic Therapy (PDT) is a mechanism that inactivates cells and microorganisms through photosensitization. Energy is absorbed and transferred between molecules, leading to increased oxidative stress. The use of PDT in endodontic treatment has been recommended to reduce its bacterial load. Furthermore, for regenerative endodontic procedures (REPs), various photobiomodulation protocols have been assessed, mainly using in vitro models with dental pulp cells, to optimize the release of signaling molecules and, consequently, establish the most favorable regenerative niche for REPs outcomes. Most protocols employing low-intensity red lasers have shown promising effects on stem cell migration and differentiation, potentially supporting the tissue regeneration process. Photobiomodulation has also been used to enhance tissue response to dental materials and/or procedures, offering comfort and enhancingpatients' quality of life. From this perspective, photobiomodulation shows potential benefits for postoperative pain control after endodontic treatment, improving bone quality formation, tissue integration with biomaterials, and tissue repair in direct pulp capping. This chapter will discuss the use and benefits of photobiomodulation across various applications within Restorative Dentistry.